Development of a Pericapsular Knee Desensitization Technique in Dogs: An Anatomical Cadaveric Study - Marta Garbin; Raiane A. Moura; Yasmim C. Souza; Mariana Cavalcanti; Adam W. Stern; Marta Romano; Enzo Vettorato; Pablo E. Otero; Diego A. Portela (Veterinary Sciences, 2025)
Regional anesthesia techniques targeting articular nerve branches offer promising avenues for managing articular pain. This study developed and compared the success rates of an ultrasound-guided versus a blind pericapsular knee desensitization (PKD) technique in canine cadavers. In Phase I, gross dissection and ultrasound evaluations were performed in eight limbs to characterize the anatomy of the medial (MAN), lateral (LAN), and posterior (PAN) articular branches of the saphenous, common fibular, and tibial nerves, respectively, and to identify suitable anatomical and ultrasonographic landmarks. In Phase II, ultrasound-guided and blind PKD injections of a dye solution were randomly performed in 10 cadavers (20 limbs), followed by dissection and histological assessment of staining accuracy. The ultrasound-guided technique achieved a significantly higher overall success rate (96.7%) than the blind technique (73.3%; p = 0.02). The MAN was successfully stained in 100% of ultrasound-guided and 50% of blind injections (p = 0.03), while the LAN and PAN were stained with high but comparable success. Parent nerve involvement was minimal for MAN and PAN but frequent for the common fibular nerve following LAN injections. Histological confirmation supported the anatomical findings, although PAN identification remained inconsistent. These results support the feasibility and increased precision of ultrasound-guided PKD, providing a foundation for further clinical evaluation.